Impact of digital twin adoption on food supply chain performance: a system dynamics approach - Huang, Ying; Ghadge, Abhijeet; Yates, Nicky (Taylor & Francis, 2026)
Digital Twin (DT) technology provides a promising solution to challenges within the food supply chain (FSC) due to its unique characteristics. While existing literature highlights the potential of DTs to enhance real-time monitoring, predictive analytics, and operational efficiency, a quantitative assessment of the overall impact of DT implementation on FSC performance is missing. This study bridges this research gap by integrating experimental and analytical approaches. Empirical data were collected through questionnaires from food industry practitioners, combined with literature to develop a mental model for capturing the interrelationships among DT-relevant technologies, FSC operations, and supply chain performance. Later, by deploying systems thinking and system dynamics (SD) modelling approaches, the impact of DT adoption on FSC operational metrics is evaluated. The findings indicate that the DT positively impacts inventory levels, actual delay (lead time), and unfulfilled orders in the short term, while contributing to cost reduction and food waste in the long term. The SD models not only highlight the impact of integrative technology adoption on the operations of FSCs but also provide a comprehensive framework for modelling and assessing SC systems under the influence of technology. This study contributes by providing quantitative evidence of DT's impact on the FSC.
Keywords: Operations Research; Digital Twin; supply chain performance; food supply chains; system dynamics